Transnational higher education by German universities: Main drivers and components - Nadin Fromm (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2014)
Transnational education plays a key role in the current debate on the internationalization of higher education, and represents one response to the burgeoning growth in worldwide demand for tertiary education. The main focus of the present paper is on provider and institutional mobility in tertiary education, concentrating on the case of German higher education institutions. This paper studies the existing federal program responsible for the development and organization of transnational study programs. Empirical data is presented along with German-backed universities, which are discussed as one possible means for Germany to provide transnational higher education abroad. This paper introduces various political dimensions that may be included in the development of binational universities and presents them as a preliminary result of the burgeoning diffusion of tertiary education. – – In der wissenschaftlichen Debatte zur Internationalisierung von Hochschulbildung spielt die Transnationalisierung gegenwärtig die zentrale Rolle und wird als eine mögliche Antwort auf die stark wachsende Nachfrage weltweit nach Tertiärer Bildung diskutiert. Im folgenden Beitrag steht die sog. Einrichtungs- sowie Institutionenmobilität - als mögliche Ausprägungen von Transnationalisierung - im Mittelpunkt des wissenschaftlichen Interesses. Vor dem Hintergrund deutscher Aktivitäten werden der Begriff sowie das dahinterstehende Konzept von Transnationalisierung beschrieben. Dazu stellt der Artikel ein bestehendes öffentliches Programm vor, in dessen Rahmen transnationale Hochschulbildungsangebote mit deutscher Unterstützung im Ausland aufgebaut werden. Zuletzt entstanden so sog. German-backed universities, welche im internationalen Vergleich als besonders gelten können. Empirische Daten werden präsentiert, welche - mit Blick auf die Implementierung - den Typ näher beschreiben und auf die Wesensmerkmale eingehen. So wird die Implementierung der binationalen Hochschulen durch politische Motivationen und Treiber bestimmt, welche auch Gegenstand des vorliegenden Beitrags sind.
Keywords: 300; transnational higher education; definitions and approaches; provider and institutional mobility by German universities; implementation settings